2019
DOI: 10.4103/jfmpc.jfmpc_492_19
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of facilitators and barriers to cardiovascular risk factor control in a semiurban population in India

Abstract: Cardiovascular (CV) risk factors like diabetes and hypertension are poorly controlled in both rural and urban India. This study was designed to identify the reasons for suboptimal control in a semiurban population in India. A total of 70 participants from the Study to Expand Heart Associated Treatments (SEHAT) trial, conducted in West Bengal, India. We qualitatively examined perspectives regarding CV risk factor control using focus group discussions based on the theory of reasoned action. Qualitative content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
2
1
1
Order By: Relevance
“… 27 Similarly, Satish et al conducted qualitative interviews with hypertensive patients in the semiurban city of Dalkhola, West Bengal, and found that few respondents acknowledged a link between hypertension the risk of heart attacks or stroke. 18 We hypothesised that individuals who were aware of the serious consequences of hypertension would find hypertension control more salient and thus be more likely to take daily treatment; however, we found no association between knowledge of hypertension consequences and daily treatment use. Since this was a descriptive finding, rather than a causal one, an important focus of future intervention work will be to determine if improving individuals’ knowledge of hypertension consequences increases their probability of daily treatment.…”
Section: Discussioncontrasting
confidence: 58%
“… 27 Similarly, Satish et al conducted qualitative interviews with hypertensive patients in the semiurban city of Dalkhola, West Bengal, and found that few respondents acknowledged a link between hypertension the risk of heart attacks or stroke. 18 We hypothesised that individuals who were aware of the serious consequences of hypertension would find hypertension control more salient and thus be more likely to take daily treatment; however, we found no association between knowledge of hypertension consequences and daily treatment use. Since this was a descriptive finding, rather than a causal one, an important focus of future intervention work will be to determine if improving individuals’ knowledge of hypertension consequences increases their probability of daily treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…From these records, we retrieved 33 articles, and after going through the full text of these articles, 18 studies were included in the review (figure 1). 26–43…”
Section: Resultsmentioning
confidence: 99%
“…Kurangnya pengetahuan tentang penyakit hipertensi sehingga tidak mematuhi pengobatan menyebabkan konsekuensi negatif dari hipertensi yang tidak terkontrol. Selain itu mungkin masyarakat telah memahami pentingnya kontrol tekanan darah tetapi tidak mengetahui terkait terapi minum obat setiap hari yang merupakan cara yang paling efektif untuk mengontrol tekanan darah (Satish et al, 2019). Sebuah studi yang dilakukan di Chennai, menunjukkan bahwa sekitar 1/3 orang dewasa yang terdiagnosis hipertensi tidak minum obat setiap hari.…”
Section: B Pembahasanunclassified